2001
DOI: 10.1074/jbc.m007136200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Tight Junction Permeability and Occludin Phosphorylation by RhoA-p160ROCK-dependent and -independent Mechanisms

Abstract: In epithelial and endothelial cells, tight junctions regulate the paracellular permeability of ions and proteins. Disruption of tight junctions by inflammation is often associated with tissue edema, but regulatory mechanisms are not fully understood. Using ECV304 cells as a model system, lysophosphatidic acid and histamine were found to increase the paracellular permeability of the tracer horseradish peroxidase. Cytoskeletal changes induced by these agents included stimulation of stress fiber formation and myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
185
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(206 citation statements)
references
References 52 publications
19
185
0
2
Order By: Relevance
“…Like claudins, OCLN is a component of tight junction strands (7), but strands also form in OCLN-deficient cells (8), and the complex phenotype of OCLN -/-mice is not clearly related to tight junction abnormalities (9). However, phosphorylation of the cytoplasmic domain of OCLN correlates with tight junction formation (33) and has been shown to regulate junction permeability (34). Both external loops, as well as the transmembrane and the cytoplasmic domains of OCLN, are important for regulation of paracellular permeability (35), and studies have also shown that OCLN is responsible for sealing of tight junctions (36).…”
Section: Discussionmentioning
confidence: 99%
“…Like claudins, OCLN is a component of tight junction strands (7), but strands also form in OCLN-deficient cells (8), and the complex phenotype of OCLN -/-mice is not clearly related to tight junction abnormalities (9). However, phosphorylation of the cytoplasmic domain of OCLN correlates with tight junction formation (33) and has been shown to regulate junction permeability (34). Both external loops, as well as the transmembrane and the cytoplasmic domains of OCLN, are important for regulation of paracellular permeability (35), and studies have also shown that OCLN is responsible for sealing of tight junctions (36).…”
Section: Discussionmentioning
confidence: 99%
“…The membranes were subjected to immunoblotting as described previously. 12 Immunofluorescence and confocal microscopy Cells cultured on coverslips were fixed with 3% paraformaldehyde for 15 min and then rinsed with phosphate buffered saline. The cells were permeabilized for 15 min with phosphate buffered saline containing 0.5% Triton-X.…”
Section: Gel Electrophoresis and Immunoblottingmentioning
confidence: 99%
“…Occludin dephosphorylation may increase tight junction permeability independently of the changes in surface charge and actin cytoskeleton that also are associated with endothelial barrier dysfunction (28,54).…”
Section: Vitamin C Therapy For Sepsismentioning
confidence: 99%